Bronchoscopic lung volume reduction - M. I. Polkey; N. S. Hopkinson (European Respiratory Review, 2006)
Surgical lung volume reduction can improve exercise performance and forced expiratory volume in one second in patients with emphysema. However, the procedure is associated with a 5% mortality rate and a nonresponse rate of 25%. Accordingly, interest has focused on alternative ways of reducing lung volume. Two principle approaches are used: collapse of the diseased area using blockers placed endobronchially and the creation of extrapulmonary pathways. Preliminary data from the former approach suggest that it can be successful and that the magnitude of success is related to reduction in dynamic hyperinflation.